Visual comfort with different correlated colour temperature among Presbyopia / Muhamad Illias Nor Azmi - Nor Azmi, Muhamad Illias (2016)
Purpose: To assess and compare the visual comfort with three (3) different correlated colour temperature among presbyopia. Materials and methods: 14 subjects among elderly aged from 37 to 59 years old recruited randomly from the area of Kuala Selangor, Selangor. The subject was asked to read the largest notation size of words until the smallest notation size of UiTM near reading chart in three (3) different correlated colour temperatures (2,856K, 4,100K, and 5,600K). The questionnaire is given and the subject needs to respond their feedback regarding the visual comfort based on the rating scale. Results: The 2,856K lamp provided the least visual comfort at all. The finding shows that 2,856K lamp was rated least favourably in every aspects of the questionnaire. It was rated particularly low on psychological indicators such as how the participants liked the colour of the lamp, on physiological indicators of the light bothering their eyes, giving them headaches, making them sleepy or tired, and making them uncomfortable. However, most of the subject response on both types of 4,100K and 6,500K colour temperature were rated similarly for certain questions. Seven (7) out of (9) question shows no significance different between this colour temperature. The subject had scored with high rating scale, means that they are least favourable towards the question asked. Conclusion: The best visual comfort that can be obtained from the two colour temperature, which were within 4,100K and 6,500K.